Peran Masjid dalam Membentuk Nilai Nilai Toleransi pada Masyarakat Pluralisme (Studi Kasus di Masjid Nurul Jannah Petro Gresik) - Lailatul Fitroini; Muhammad Farih (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this research is to understand the role of the Nurul Jannah Mosque in developing the value of tolerance in a pluralistic society, as well as analysing the methods and implementation applied by the mosque in creating inter-religious harmony. This research uses a qualitative approach with the type of field research, which focuses on direct observation in the field and interviews with mosque administrators, community leaders, and worshipers. This research seeks to explore in depth how the Nurul Jannah Mosque contributes to shaping tolerance awareness in a heterogeneous society in Gresik. The results show that the Nurul Jannah Mosque plays a very important role in the social life of the community, especially in developing the value of tolerance among people of different religions. This mosque not only functions as a place of worship, but also as a centre for social activities, education, da'wah, and economic empowerment. One concrete example of the role of tolerance shown by the mosque is the freedom for religious people to carry out worship according to their respective beliefs, without any discrimination. In addition, the Nurul Jannah Mosque actively holds studies by presenting speakers from different Islamic organisations, which help enrich insight and strengthen the bond of brotherhood between people. Overall, this research shows that the Nurul Jannah Mosque not only plays a role in the spiritual aspect, but also as a facilitator that fosters the value of tolerance and pluralism in the community. The activities carried out by this mosque are a clear example of how places of worship can function as inclusive spaces that encourage the creation of interfaith harmony in a plural society.